Social Capital and Dengue Fever Management In Buang Ngern Subdistrict, Thailand : A Case Study - Asri, Asri; Nuntaboot, Khanitta; Reliani, Reliani (Jurnal Keperawatan Muhammadiyah, 2018)
Objective Â to describe the existence of social capital in managing dengue fever in buang ngern subdistrict, Thailand. Method this study use case study based on the thepry pof social capital as the foundation of the data analysis Result In the case study on Buang Ngern shows that the community which have high level of social capital could be able to reduce the incidence of dengue fever significantly by cooperating with various sectors, such as; Household Members, Housewife Group, Village Health Volunteers, Local Administrative Organization, Village Committee Health, Health Volunteers And Health Workers In Health Centers. Cooperation which involving several community groups will be difficult to occur in the absence of a high level of trust between groups, social norms and networks among community members.Conclusion Social capital as one of the features that exist in the community is having advantage if could be used appropriately. In the community basedÂ  dengue fever prevention and control program which require inter-sectoral cooperation, social capital can become a bridge between groups in giving contribution based on the role and function of each group.